Evaluation of Rhodamine B as a biomarker for assessing bait acceptance in wild pigs. (18th December 2014) - Beasley, James; Webster, Sarah C.; Rhodes, Olin E.; Cunningham, Fred L.
ABSTRACT: Worldwide, there is growing interest in the use of pharmaceutical baits to control populations of wild pigs ( Sus scrofa ). In this study we evaluated the utility of Rhodamine B (RB), a chemical marker commonly used in wildlife research and management, as a potential biomarker for quantifying bait uptake in wild pigs. Thirty wild pigs were live‐trapped, transported to a captive facility on the Department of Energy's Savannah River Site located in South Carolina, USA, during autumn 2013, and administered RB orally at a dosage of 30 mg/kg. Eight vibrissae and guard hairs were collected pre‐ and post‐RB exposure (7 or 14 days) and evaluated for the presence of RB using fluorescence microscopy. No evidence of RB marking was observed in any samples collected pre‐RB administration. In contrast, we observed fluorescent marking post‐RB exposure that was indicative of the presence of RB for all individuals, with 98% of vibrissae and 100% of guard hairs exhibiting RB marks. The uniform detection of RB among individuals and consistent manifestation of marks in both guard hair and vibrissae, samples that easily can be collected and stored by untrained field personnel from live or deceased pigs, suggests that RB is an effective biomarker for use in large‐scale management programs to control wild pigs. In particular, our results, combined with previous studies evaluating uptake of RB in other species, suggest that RB can be used to develop baiting programs to deliver pharmaceuticals to free‐ranging wild pigs, as well as evaluate the potential impacts of pig baits on non‐target species. © 2014 The Wildlife Society.